Antidiarrhoeal, antimicrobial and antioxidant effects of myrtle berries (Myrtus communis L.) seeds extract. (15th December 2015) - Jabri, Mohamed‐Amine; Rtibi, Kais; Ben‐Said, Amira; Aouadhi, Chedia; Hosni, Karim; Sakly, Mohsen; Sebai, Hichem
Abstract: Objectives: The present study was carried out to determine the antidiarrheal effects of myrtle ( Myrtus communis L.) berries seeds aqueous extract (MBSAE) from Tunisia as well as the involvement of its antimicrobial and antioxidant properties in such protection. Methods: Adult male wistar rats were used and divided into six groups of ten each: control, Castor oil, Castor oil + Loperamide and Castor oil + various doses of MBSAE. Animals were per orally ( p.o .) pre‐treated with MBSAE for one hour and intoxicated by castor oil acute oral administration. Key findings: Our results demonstrated that the MBSAE is rich in total and condensed tannins and exhibited a broad spectrum of antibacterial activity. In vivo, we found that MBSAE administration induced a significant dose‐dependent protection against diarrhoea and intestinal fluid accumulation. Castor oil‐induced intestinal hypersecretion was accompanied by an oxidative stress status in the intestine. More importantly, we showed that acute diarrhoea was accompanied by an increase in intestinal mucosa hydrogen peroxide (H2 O2 ), calcium and free iron levels while MBSAE pre‐treatment reversed all castor oil‐induced intracellular mediators disturbances. Conclusions: We suggest that MBSAE had a potent protective effects against castor oil‐induced acute diarrhoea due in part to its antioxidant and antimicrobial properties.